PENISTAAN/PENODAAN AGAMA DALAM PERSPEKTIF PEMUKA AGAMA ISLAM DI DKI JAKARTA - M. Taufik Hidayatulloh (Harmoni, 2014)
This study aims to: (1) Understand and analyze levels of understanding amongst religious leaders on the contents of Law No. 1 / PNPS / 1965; (2) Understand and analyze the concept of religious leaders on the definition of blasphemy; (3) Understand and analyze the perspetives of religious leaders on the punishment that should be given to those who commit religious defamation; (4) Understand and analyze the principal religious teachings from the perspective of religious leaders; and (5) Understand the responses of religious leaders on the implementation of Law No. 1 / PNPS / 1965. This is a qualitative study that looks as the opinions of religious leaders. It was conducted in Jakarta in 2013. Subjects of the study were elected Islamic religious leaders. The results showed that only a few religious leaders who knew the Law No. 1 / PNPS / 1965. These leaders criticized the way some of the concepts were operationalized and implemented by the government, which has not implemented the legislation in a way that has satisfied most parties.